Refinamento de dados de altimetria por satélite medidos ao longo da costa brasileira - Daher, Victor Bastos (2019)
A satellite altimetry data processing methodology has been developed and applied for the calculation of Sea Surface Height Anomalies (SSHA) for assimilation in hydrodynamic models. The region of interest is limited by latitudes of 12°S and 34°S and longitudes of 54°W and 32°W. For this, the results of the main tide models FES2014, TPXO9 and GOT4.8 used to estimate the ocean tide correction applied to satellite data were analyzed. A new tidal correction calculated based on the results of regional hydrodynamic modeling using the HYCOM model was inserted in the comparison of the models mentioned above. In this context, a method of extracting from the HYCOM results only the barotropic sea surface height was tested. The definition of a cutoff wavelength of the filter used to eliminate the short wavelength noise present in the satellite data was based on the study of the wavelength of the baroclinic tide in the study region. This calculation was made using satellite data and, for this, a tidal harmonic analysis was tested. The results indicate that the tide models produce results with average differences of 4 cm and TPXO9 is the model that presents results closest to the tide gauges. Harmonic analysis of satellite data is robust enough to estimate the main tidal components with values no further than 4 cm from the tidal models. Thus, the application of this analysis made it possible to define the wavelength of the M2 baroclinic tide constituent, 140 km. The resulting AASM were compatible with DUACS and ATOBA AASM, but with a higher energy preservation on signals with wavelengths greater than 140 km.